RASIO KEUANGAN DALAM MEMPREDIKSI LABA PADA MASA YANG AKAN DATANG - Ibnu Pratama, 0425030136; Kartika, Andi (Students Journal of Accounting and Banking, 2012)
This study aims to find out financial ratios in predicting earning changes manufacturing firms period 2007-2009. There are 5 financial ratios [ Long Term Debt Equity (LTD), Net Income to Net Worth (NINW), Inventory Turn Over (ITO), Gross Profit Margin (GPM), and Net Income to Sales (NIS). Factor analysis is used to find out financial earnings in predicting earning changes.Data in this study are from manufacturing firms listed on Indonesian stock exchange during 2007-2009. The empirical results show that Long Term Debt Equity (LTD), and Net Income to Net Worth (NINW) capable be used to predicting earning changes in future. While Inventory Turn Over (ITO), Gross Profit Margin (GPM), and Net Income to Sales (NIS) uncapable to predicting earning changes in the future.Keyword: earning changes, Long Term Debt Equity (LTD), Net Income to Net Worth (NINW), Inventory Turn Over (ITO), Gross Profit Margin (GPM) and Net Income to Sales (NIS)